Reproductive cycle in an imposex-affected population of Olivancillaria deshayesiana (Gastropoda: Olividae) from Mar del Plata, Argentina - Teso, Silvia Valeria (2012)
Olivancillaria deshayesiana (Gastropoda: Olividae) is distributed from Ilha Grande (Rio de Janeiro, Brazil) to Necochea (Buenos Aires, Argentina). Apart from some descriptions of the embryonic development and the egg capsules, little is known about the reproduction and ecology of this species. In this 2 yr study (October 2005 to September 2007), the reproductive cycle of O. deshayesiana was examined in a population highly affected by imposex, from the Mar del Plata coast, Argentina. Males exhibited seasonal reproductive activity, with a major spawning period from September to January (spring to early summer) for the 2 yr, which coincided with an increase in seawater temperature and photoperiod. In contrast, females were mature and capable of spawning year round, with a major spawning period from September to January (spring to summer), simultaneous with the major spawning period of males.